Knowledge, attitudes and practices towards malaria in a peri-urban Cameroonian village: Persistent silent transmission despite satisfactory awareness - Steve Joko; Yacouba Poumachu; Rehema Ouko; Nelly Armanda Kala-Chouakeu; Roland Bamou; Emmanuel Elanga-Ndillé; Parfait Awono-Ambene; Christophe Antonio-Nkondjio; Timoléon Tchuinkam; Cyrille Ndo (PLoS ONE, 2026)
Malaria remains a major cause of morbidity and mortality in sub-Saharan Africa, including Cameroon, despite ongoing control efforts. Knowledge, Attitudes, and Practices (KAP) studies are essential for identifying behavioural determinants of persistent transmission in communities especially in those of rural areas. To assess knowledge, attitudes, and practices (KAP) towards malaria in a Cameroonian village and investigate their association with parasitological prevalence in a peri-urban Cameroonian village and investigate their association with parasitological prevalence, highlighting silent transmission in the population. A cross-sectional study was conducted in Emana village (Cameroon) involving 249 participants for parasitological screening (microscopy) and a subgroup of 104 with complete sociodemographic data. KAP scores were analysed using non-parametric tests (Mann-Whitney U, Kruskal-Wallis H, Spearman correlation). Malaria prevalence was evaluated using chi-square tests and univariate logistic regression. Categories were regrouped when necessary for complementary analyses. Knowledge and attitudes were generally satisfactory and homogeneous across the population, with no significant association with sociodemographic factors (all p > 0.05). Practices were generally poor but significantly better among women than men (p = 0.014). Overall malaria prevalence was 24.9%, significantly higher in the 5–18 years age group (13.25%, p = 0.027), highlighting silent and persistent transmission in this age bracket. No significant associations were observed with occupation or household size; education showed heterogeneous trends depending on category grouping. Despite satisfactory knowledge and positive attitudes, a persistent knowledge-to-practice gap exists, across subgroups, contributing to silent transmission. These findings support targeted interventions: strengthened messaging, and enhanced surveillance in all categories particularly the 5–18 years age group. Complementary qualitative studies could further explore specific practical barriers.